ECONOMIC AND LEGAL MECHANISM OF RESTRICTION ON CITIZENS' RIGHTS TO INFORMATION IN ORDER TO ENSURE NATIONAL SECURITY - Shinkar , Tetiana (Honor and Law, 2022)
The author analyzes the economic and legal mechanism of restricting the rights of citizens to information in the interests of national security, namely such elements as organizational and legal and regulatory. It is determined that after the adoption of the Law of Ukraine «On Sanctions» the application of economic sanctions to television and radio companies and Internet providers, in addition to the court and the National Council of Ukraine on Television and Radio Broadcasting, became possible by the National Security and Defense Council, the President of Ukraine and the Verkhovna Rada. Due to this, in Ukraine there is on the one hand an economic and legal mechanism for restricting the rights of citizens to information in normal conditions, and on the other hand in crisis situations that threaten the national security of Ukraine. It was the comparison of these two economic and legal mechanisms that made it possible to determine the difference between economic sanctions and sanctions applied in the event of a threat to national security, including restrictions on the information sphere. It is determined that the content of special economic and other restrictive measures can be considered administrative and economic ones, but the classification of sanctions under the Law of Ukraine «On Sanctions» to administrative and economic, the issue is quite ambiguous, as the law «On Sanctions» uses the term «special economic and other restrictive measures», and not economic sanctions or administrative and economic sanctions. In addition, the mechanism of economic and legal restriction of information rights through the application of sanctions provided by the laws «On Television and Radio Broadcasting» and «On Sanctions» differs in the order of restriction, types of sanctions to which subjects apply sanctions and authorities authorized to impose sanctions. It is determined that according to the subjects to which special economic and other restrictive measures are applied, there are sanctions against a foreign state or an indefinite number of persons of a certain type of activity (sectoral sanctions) and sanctions against certain legal or natural persons, as well as entities that carry out terrorist activities (personal sanctions). It is concluded that despite the need to apply special economic and other restrictive measures to protect national security, the Constitutional Court of Ukraine needs clarification of the law of Ukraine «On Sanctions» on the constitutionality of the law «On Sanctions», decrees of the President of Ukraine, Resolutions of the Verkhovna Rada of Ukraine), the Supreme Court of Ukraine on the procedure for proving the threat to national security, the list of entities to which appropriate sanctions may be applied, the content and nature of «special economic and other restrictive measures», the procedure for appealing decisions on sanctions, etc.